The founders of the Kyiv Physical-Mathematical Society: Mikhailo Petrovich Avenarius (1835–1895) - Kletska, T. S. (History of science and technology, 2018)
This article highlights the life and work of the Kyiv outstanding physicist and educator Mikhailo Petrovich Avenarius, who made a great contribution to the development of physics education in Ukraine. Avenarius was one of the founders of Kyiv Physical-Mathematical Society. Based on archival sources, scientific publications and memoirs of his colleagues and students, the main stages of his biography have been restored and his professional career has been examined. His work at the Kyiv University of St. Vladimir has been detailed throughout 25 years, as well as his achievements as a scientist, teacher and popularizer of science.